PENGARUH PENGGUNAAN MODEL KEPALA BERNOMOR TERHADAP HASIL BELAJAR IPA PESERTA DIDIK DI SEKOLAH DASAR - Maura Edita; Hery Kresnady; Nuri Sidauruk (Universitas Tanjungpura, 2019)
AbstractThis research aims to analyze the effect of the use of the model results against the numbered head learning natural science learners class V 15 State primary school South Pontianak. The method used is the method of experimentation. This research uses Quasi experimental research that is Experimental Design with form Time Series Design. The population in this research is the entire learners class V 15 State primary school South Pontianak. Sampling techniques using the technique of Nonprobability Sampling technique with Convenience Sampling. Then the sample in this research is the entire learners class V (classroom experiment) with the amount of 21 learners. Data collecting techniques used are measurement techniques. Data collecting tool used namely in the form of tests. Based on the analysis of data obtained average results pre-test learners of 62.23 and results the average post-test learners of 68.52. After the test is done t thitung of 4.9453 is obtained, while ttabel with db = 21 – 1 = 20 and extent of significant (α) = 5% is 1.725, turns thitung ≥ ttabel or 4.9453 ≥ 1.725, then Ha received. So, it can be concluded that there is an influence of the use of the Model results against the numbered head learning natural science learners class V 15 State primary school South Pontianak. Based on the results of the calculation of effect size () = 0.47 earned that belongs in the category are in the range of An effect size of 20 is medium. Thus it can be said that the use of the numbered head Models provide the influence that being against the results of the study of natural science learners class V SD Negeri Pontianak 15 South. Keywords: The Use Of Numbered Head Model, The Results Of The Study Participants, The Nature Of Science.